ANALISIS HUBUNGAN FAKTOR-FAKTOR KUALITAS PELAYANAN DENGAN KINERJA PELAYANAN - Tiara Yulizar Puteri; Otong Karyono; Kania Agustina Pahlawani (Universitas Majalengka, 2022)
This research aims to analyze the relationship between service quality factors and service performance carried out in the Bogor Regency Regional Secretary environment. This research uses quantitative methods with data collection techniques through research questionnaires distributed to 164 employees who have the task of providing services, with the analysis technique used is multiple correlation analysis. The results of the study prove empirically that the quality factors of service have a significant relationship with service performance